Chemotaxonomic survey of Malaysian Mimosa species - Yusof, Umi Kalsom; Abdullah, Faridah; Abdullah, Noriha; Itam, Khairuddin; Bakar, Baki; Sukari, Mohd Aspollah (Penerbit Universiti Kebangsaan Malaysia, 2003)
Flavonoids of four Malaysian Mimosa species were analysed. Quercetin 7-methyl ether was found in all four Mimosa species, kaempferol, apigenin and acacetin were detected in M. pigra and M. invisa Orientin was the only flavone C-glycosides detected in M. pudica. Both M. pigra and M. invisa synthesized quercetin 3-rhamnoside, quercetin 3-rutinoside, quercetin 3, 7-dirhamnoside, kaempferol 3-rhamnoside, kaempferol 3,7-dirhamnoside and luteolin 7-arabinoside. Flavonoid patterns of M. pudica differs from M. longihirsuta as the former species synthesized kaempferol 7-rutinoside and kaempferol 3-glucoside-7-rhamnoside, and the latter species produced quercetin 3-glucoside-7-rhamnoside.